1999
DOI: 10.1111/j.1151-2916.1999.tb02272.x
|View full text |Cite
|
Sign up to set email alerts
|

Young's Modulus and Compositional Parameters of Oxide Glasses

Abstract: The Young's moduli of various oxide glasses (silicate, borate, phosphate, and tellurite) were measured using an ultrasonic method. To predict the Young's moduli of the oxide glass systems, empirical compositional parameters Gi and Vi, based on the Makishima‐Mackenzie theory, were obtained, where Gi is the dissociation energy and Vi the packing density parameter of a single‐component oxide. The relationship between the calculated Young's modulus from the compositional parameters and the measured Young's modulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(134 citation statements)
references
References 21 publications
(15 reference statements)
6
128
0
Order By: Relevance
“…Recently it has been observed that the structural strength of these glasses is increasing with the degree of connectivity in the glass [30,[36][37][38][39]. Baikova et.al.…”
Section: Insights In the Tribochemistry Of Zndtpsmentioning
confidence: 99%
“…Recently it has been observed that the structural strength of these glasses is increasing with the degree of connectivity in the glass [30,[36][37][38][39]. Baikova et.al.…”
Section: Insights In the Tribochemistry Of Zndtpsmentioning
confidence: 99%
“…Experimental values of density, molar volume, and ratio of the molar volumes V m (BO 4 )/V m (BO 3 ) which was calculated according to Kodama et al [23] using fractions of BO 4 units (N 4 ) values (almost equals 0.5) calculated theoretically according to Inaba et al [24] are tabulated in Table II. The density value of pure lithium borate glass composition (sample A) is 2230 kg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…O where R A and R O are the Pauling ionic radii of metal and oxygen ions, respectively [35][36][37]. Densities of all the glasses (NBP, NBB and NBT) increase with increase in the concentration of PbO, Bi 2 O 3 or TeO 2 while their molar volumes decrease.…”
Section: Resultsmentioning
confidence: 99%